2014
DOI: 10.1530/ec-14-0036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of increased resistant starch consumption in human type 2 diabetes

Abstract: Resistant starch (RS) has been shown to beneficially affect insulin sensitivity in healthy individuals and those with metabolic syndrome, but its effects on human type 2 diabetes (T2DM) are unknown. This study aimed to determine the effects of increased RS consumption on insulin sensitivity and glucose control and changes in postprandial metabolites and body fat in T2DM. Seventeen individuals with well-controlled T2DM (HbA1c 46.6±2 mmol/mol) consumed, in a random order, either 40 g of type 2 RS (HAM-RS2) or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 36 publications
7
128
0
5
Order By: Relevance
“…Interestingly, resistant starch supplementation increases peripheral glucose uptake in healthy subjects and in subjects with the metabolic syndrome [37] ; yet, a subsequent study by the same authors found no effect using the same method in subjects with DMT2 [38] , a finding that supports earlier work indicating that the underlying pathophysiology of diabetes may attenuate the effect of FCHO on glucose metabolism [39] . We have recently shown that over 9 weeks, the same dose of inulin as used in this study (30 g/day) reduces FPG in subjects with prediabetes compared to control [unpublished data], suggesting that longer supplementation periods may be required in subjects with prediabetes or DMT2.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Interestingly, resistant starch supplementation increases peripheral glucose uptake in healthy subjects and in subjects with the metabolic syndrome [37] ; yet, a subsequent study by the same authors found no effect using the same method in subjects with DMT2 [38] , a finding that supports earlier work indicating that the underlying pathophysiology of diabetes may attenuate the effect of FCHO on glucose metabolism [39] . We have recently shown that over 9 weeks, the same dose of inulin as used in this study (30 g/day) reduces FPG in subjects with prediabetes compared to control [unpublished data], suggesting that longer supplementation periods may be required in subjects with prediabetes or DMT2.…”
Section: Discussionsupporting
confidence: 52%
“…We have recently shown that over 9 weeks, the same dose of inulin as used in this study (30 g/day) reduces FPG in subjects with prediabetes compared to control [unpublished data], suggesting that longer supplementation periods may be required in subjects with prediabetes or DMT2. Nevertheless, the effect of FCHO on glucose metabolism is clearly complex, with the type of FCHO (resistant starch, fructooligosaccharides, lactulose or inulin) [7,8,32] , the SCFA ratio produced [40] , and underlying pathophysiology [38,39] all appearing to mediate the effect of FCHO. We would draw particular attention to establish in vivo, the metabolic fate of the SCFAs: randomized controlled trials have shown that oral propionate lowers fasting and postprandial glucose [41,42] ; yet acute gastric infusion of propionate has no effect on hepatic glucose production or glucose levels [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Resistant starch has been proved to exhibit potential health benefits, including reducing the glycemic response [6], lowering blood cholesterol [7], acting as a functional probiotic [8], and increasing the production of short chain fatty acids in the large intestine [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the unphysiologically high concentrations of sodium propionate applied in these studies advise caution. Bodinham et al [156] recently studied the effects of increased resistant starch consumption in type-2 diabetes patients. While insulin sensitivity did not improve, a benefi cial effect on meal handling behavior was observed.…”
Section: Propionic Acidmentioning
confidence: 99%
“…Moreover, many studies performed in humans used a SCFA mix [161] or prebiotics such as resistant starch [156]. In consequence, it is not possible to separate the effects of the SCFAs and to analyze any synergistic or antagonistic actions.…”
Section: Propionic Acidmentioning
confidence: 99%